Study on Safety Culture Following the Implementation of a Near-Miss Management System in the Traditional Manufacturing Industry - Maria H. Pedrosa; Ana K. Salazar; Carla Cardoso; Joana C. Guedes (Safety)
Safety culture is crucial for organisations aiming to enhance safety performance and is challenging in traditional sectors. This study explored the effects of a new near-miss management system (NMS) on safety culture in traditional manufacturing companies. The data collection followed a mixed-methods design: quantitative data were collected through pre- and post-implementation surveys, and qualitative data were derived from focus group discussions (FGDs) developed a year after NMS implementation in two footwear companies. After that period, it is possible to infer that the NMS led to changes in the safety culture. OHS management commitment, accident and near-miss investigation, and OHS meetings and training dimensions were impacted. Employees perceived the NMS introduction as a signal of management′s commitment and the possibility of accessing training and participating in near-miss and accident investigations. In organisations that rely on intensive manual labour, ongoing training is essential to ensure that safety measures are effective and that the organisation′s safety management system (NMS) is sustainable. Although limited by the small sample size and sector focus, the results show that even a simplified NMS procedure adapted to the company and adequate training provided to the workforce significantly impacts the company′s safety culture and workers′ safety behaviour.